Micro-based evidence of EU competitiveness: the CompNet database - Paloma Lopez-Garcia; Filippo di Mauro; Nicola Benatti; Chiara Angeloni; Carlo Altomonte; Matteo Bugamelli; Leandro D'Aurizio; Giorgio Barba Navaretti; Emanuele Forlani; Stefania Rossetti; Davide Zurlo; Antoine Berthou; et al. (European Central Bank (ECB), 2014)
Drawing from confidential firm-level balance sheets in 11 European countries, the paper presents a novel sectoral database of comparable productivity indicators built by members of the Competitiveness Research Network (CompNet) using a newly developed research infrastructure. Beyond aggregate information available from industry statistics of Eurostat or EU KLEMS, the paper provides information on the distribution of firms across several dimensions related to competitiveness, e.g. productivity and size. The database comprises so far 11 countries, with information for 58 sectors over the period 1995-2011. The paper documents the development of the new research infrastructure, describes the database, and shows some preliminary results. Among them, it shows that there is large heterogeneity in terms of firm productivity or size within narrowly defined industries in all countries. Productivity, and above all, size distribution are very skewed across countries, with a thick left-tail of low productive firms. Moreover, firms at both ends of the distribution show very different dynamics in terms of productivity and unit labour costs. Within-sector heterogeneity and productivity dispersion are positively correlated to aggregate productivity given the possibility of reallocating resources from less to more productive firms. To this extent, we show how allocative efficiency varies across countries, and more interestingly, over different periods of time. Finally, we apply the new database to illustrate the importance of productivity dispersion to explain aggregate trade results.
Keywords: L11; L25; D24; O4; O57; 330; allocative efficiency; competitiveness; cross country analysis; firm-level data; productivity and size distribution; total factor productivity